Leaving us to wonder : an essay on the questions science can't ask - Wiener, Linda F., 1957- (SUNY series in philosophy and biology., 2005)
"This collaboration between a biologist and a philosopher explores the meaning of the scientific worldview and how it plays out in our everyday lives. The authors investigate alternative to scientism, the view that science is the proper and exclusive foundation for thinking about and answering every question."--Jacket